KATEGORYZACJA SWÓJ/OBCY W DEBACIE SPOŁECZNOŚCIOWEJ W KONTEKŚCIE KRYZYSU MIGRACYJNEGO W EUROPIE - Grzelak, Eliza; Szymborska, Marta (Studia Europaea Gnesnensia, 2018)
The aim of this article is to demonstrate the differences in the perception of immigrants and refugees in social debate taking place online. For that purpose, the authors analysed comments posted in social media (Facebook). When describing the techniques of categorization, attention was paid to the interlacing colloquial and scientific descriptions in the discourse concerned with contemporary migrations, also focusing on the process of neosemantization to which scientific terms are subjected.